Community adaptation and environmental changes at the Putri Cempo PLTSa, Surakarta - Bagus Amirul Huda; Agung Budi Sardjono (Eduvest - Journal of Universal Studies, 2025)
Waste management in urban areas has become a complex challenge in Indonesia, with a significant increase in national waste volume. This research aims to analyze changes in the physical quality of residential environments due to the operation of Waste-to-Energy Power Plant (PLTSa) at Putri Cempo Landfill, Surakarta, and identify community adaptation patterns to these environmental transformations. Using a descriptive qualitative approach, data were collected through in-depth interviews and field observations, then analyzed using theories of settlement quality and environmental adaptation. Results show that PLTSa significantly impacts contextual, spatial, economic, and social aspects of settlements, especially within a radius of ≤500 meters. The absence of buffer zones exacerbates the effects of air pollution and noise. Economically, the reduction in waste picking activities without adequate livelihood alternatives becomes a major problem. The community demonstrates three adaptation patterns: behavioral adjustment, independent waste management, but rarely relocation due to economic limitations. Intervention priorities should be directed toward developing buffer zones and community economic empowerment programs.